Increasing carbapenem resistance due to the clonal dissemination of oxacillinase (OXA-23 and OXA-58)-producing Acinetobacter baumannii: report from the Turkish SENTRY Program sites - KORTEN, VOLKAN (MICROBIOLOGY SOC, 2008)
A significant increase in carbapenem-resistance rates among Acinetobacter baumannii isolates collected in two Turkish medical centres was detected in the 2000-2006 period (20-60%) by the SENTRY Antimicrobial Surveillance Program. Carbapenem-resistant strains from 2006 were evaluated for the presence of encoding genes and epidemic clonality. OXA-58-like and OXA-23-like carbapenemase-producing strains were detected in both medical institutions. Seventeen out of 18 strains from Ankara were positive for bla(OXA-58) primers and belonged to the same clone, whilst 26 isolates (25 from Istanbul and one from Ankara) harboured bla(OXA-23)-like genes and showed identical or similar PFGE patterns. Isolates producing OXA-23-like carbapenemases were more resistant than OXA-58-like carbapenemase producers to non-carbapenem antimicrobial agents. Carbapenem resistance in these institutions was observed to be largely driven by the dissemination of clones producing OXA-type carbapenemases.
Keywords: BETA-LACTAMASES; BLA(OXA-23); OXA-58